Urinary bladder washings in autopsies. A cytopathologic study of 63 cases - Tani, E. M.; Montenegro, M. R.; Vana de Camargo, J. L. (Frontiers, 1983)
The sediment from urinary bladder washings from 63 consecutive autopsies was cytologically studied in order to achieve a better understanding of the changes in urothelial cells collected from hospital populations. The observed alterations were correlated with alterations in the urinary system and with therapy preceding death. The specimens obtained were of good quality. In 39.7% of the cases, the sediment contained giant superficial multinucleated cells. Three of nine cases previously subjected to radiation or chemotherapy showed atypical urothelial cells. In three cases with immunosuppression, there was cytologic evidence of subclinical infection by polyomavirus, and virus particles were identified by electron microscopy of the vesical mucosa. The study of the smear background offered additional information: the sediment contained hyaline or hematic or hyaline-cellular casts in 17.4% of the cases, in all of which there were renal tubulopathies when the kidney sections were studied. The method is useful for a good evaluation of the autopsy as well as for training in urinary cytopathology.
Keywords: autopsy; bladder; bladder epithelium; bladder irrigation; cytodiagnosis; diagnosis; histology; human; major clinical study; Adolescent; Adult; Aged; Autopsy; Bladder; Cell Nucleus; Child; Child, Preschool; Epithelium; Female; Human; Infant; Infant, Newborn; Kidney Tubular Necrosis, Acute; Leukemia; Lymphoma; Male; Middle Age; Polyomavirus